Prediction of Residual Stress Distribution in NM450TP Wear-Resistant Steel Welded Joints - Guannan Li; Guangjie Feng; Chongyang Wang; Long Hu; Tao Li; Dean Deng (Crystals, 2022)
This study developed a thermo-metallurgical-mechanical simulation method to calculate the temperature field and residual stress distribution in the NM450TP wear-resistant steel welded joints. During the simulation, the solid-state phase transformation and softening effect of NM450TP wear-resistant steel was considered. The simulation results were compared with the experimental results, which verified the feasibility of this method. The influences of solid-state phase transformation and softening effect on the welding residual stress distribution were discussed. The numerical simulation results showed that the solid-state phase transformation had a more significant effect on the magnitude and distribution of the longitudinal residual stress than that of the transverse residual stress. The softening effect had a significant influence on the peak value of the longitudinal residual stress and had little influence on the transverse residual stress. Comparing the numerical simulation results with the experimental results, it could be seen that the calculation results of the welding residual stress were in the best agreement with the experimental measurement results when the solid-state transformation and softening effects were considered at the same time.